Uveitis Is a Risk Factor for Juvenile Idiopathic Arthritis' Significant Flare in Patients Treated With Biologics - Kostik, Mikhail M.; Gaidar, Ekaterina V.; Sorokina, Lubov S.; Avrusin, Ilya S.; Nikitina, Tatiana N.; Isupova, Eugenia A.; Chikova, Irina A.; Korin, Yuri Yu.; Orlova, Elizaveta D.; Snegireva, Ludmila S.; Masalova, Vera V.; Dubko, Margarita F.; et al. (Frontiers in Pediatrics, 2022)
Objectives: Uveitis is the most frequent extra-articular manifestation of juvenile idiopathic arthritis (JIA). Our study is aimed to evaluate the possible difference in arthritis course depending on uveitis presence in JIA patients treated with biologics. Methods: From our database of JIA patients treated with biologics we extracted patients to whom the first agent was administrated with or without MTX. Exclusion criteria: treatment with current systemic corticosteroids, infliximab, rituximab, observation period less than 3 years, and no missing data. After selection, 175 patients were eligible for analysis. We evaluated clinically significant flare with joint involvement (which required change of biologic or non-biologic DMARD), time to flare. We compared two groups: i) patients with uveitis (n=32) and ii) patients without uveitis (n=143). For statistical analysis, we used Cox’s regression models, Log-Rank test, x2 test, and Mann-Whitney test. Results: there was no difference in gender distribution and achievement of arthritis remission between groups. Patients in the non-uveitis group predominantly received etanercept (64.3%). In the uveitis group, the most prescribed biologic agent was adalimumab (71.9%). The presence of uveitis increased the risk of JIA flare: OR=3.8 (95%CI:1.7; 8.7), and cumulative probability of joint flare: RR=4.5 (95%CI:1.7; 12.1), р=0.003; after adjustment on methotrexate RR=3.1 (1.6; 6.0), p=0.0008. In the subgroup of patients treated with adalimumab absence of methotrexate increased the cumulative probability of flare (RR=6.5 (95%CI: 1.4; 31.1), р=0.02). Conclusion: the presence of uveitis proved to be a risk factor for JIA flare. Methotrexate can decrease the cumulative flare probability. Further trials are required.